Desmoplastic ameloblastoma of the mandible: A rare case report - Prachi M Desai; Manisha Khorate; Nigel Figueiredo (Wolters Kluwer Medknow Publications, 2020)
Desmoplastic ameloblastoma (DA) is a rare variant of ameloblastoma that shows unique features, behavior, and presentation. This article reports a rare case of desmoplastic ameloblastoma in a 67-year-old male patient, who presented with a slow-growing, asymptomatic lesion in the anterior mandible which was observed over a period of 4 years. Radiographic findings revealed an ill-defined mixed radiolucent and radiopaque lesion with displacement of adjacent teeth. Histopathological examination showed proliferation of odontogenic cells in the form of islands separated by dense, fibrous connective tissue stroma compressing the islands. Although the incidence of this variant is very low, a differential diagnosis of the same must be taken into consideration when locally aggressive, chronic swellings of jaw are encountered in routine practice to aid in early diagnosis and in initiating a prompt management.